Effects of a multicomponent exercise program on functional capacity and quality of life of older persons in Rumah Seri Kenangan Seremban Malaysia. - Justine @ Stephany, Maria (2010)
The purpose of this study was to measure the effects of a 12-week multicomponent exercise program on functional capacity (physical functioning and psychological functioning) and quality of life of older persons residing in a public funded shelter home in Seremban, Negeri Sembilan. Forty-three subjects with mean age 70.88 + 7.82 years (exercise = 23, control = 20) participated in this quasi-experimental (pretest-posttest design study). The exercise sessions were carried out group-based three times a week, comprised of aerobic training, strength training, flexibility and balance training. Physical functioning outcome measures were cardiorespiratory endurance (6MWT), right and left armcurl strength (30-sec armcurl), right and left handgrip strength (handgrip dynamometer), lower limb strength (30-sec chairrise), right and left upper limb flexibility (backscratch), right and left lower limb flexibility (chair-sit and reach), balance performance (postural control(FRT), dynamic mobility and agility (TUG)). Psychological functioning was measured based on level of depression (12-item GDS). Quality of life was measured based on life satisfaction (Cantril’s ladder), and physical and mental component summaries of the SF-12 health survey. No significant differences were noted in all variables during the baseline measurements. At the end of the intervention, results for the exercise group revealed significant increases in cardiorespiratory endurance (41.79%), right armcurl strength (25%), left armcurl strength (30.79%), right handgrip strength (13.65%), left handgrip strength (9.93%), lower limb strength (46.19%), postural control (49.58%), dynamic balance and agility (26.37%), and physical health component summary (8.4%) (all, p < .05). The exercise group also presented with improvement in flexibility of right lower limb (63.57%), left lower limb (44.17%), right upper limb (36.67%), left upper limb (63.1%), as well as life satisfaction score (10.74%), and mental health component summary (2.95%), but all did not reach significant level ( p > .05). The control group did not improve significantly in all the measured variables. In terms of psychological functioning, both the exercise and control groups showed increase in depression scores by 1.64% and 17.7% respectively (p > .05). This study suggests that multicomponent exercise program may improve physical functioning and quality of life of institutionalized older persons.